ORGANIZATION OF PUBLISHING IN LITHUANIAN MUSEUMS: CHARACTERISTICS AND TENDENCIES - JANKEVIČIŪTĖ, LAURA (Knygotyra, 2015)
The object of this article is the publishing work of Lithuanian museums. Of late years, the problem of information circulation about the heritage of our country, the necessity of the elevation for the prestige of museums and the development of museums’ opportunities in the market of leisure are being analysed in Lithuania. Therefore, the object of this article is very relevant in the context of these problems. Analysis and researches show the role of publishing of museums: organization, characteristics, results and tendencies of improvement. A new approach to publishing as a form of museum communication reveals the current situation. The point of this article is to show the principal guidelines of publishing organization in museums and characteristics of their publications. The tasks of the article are to study the role of museum communication, it’s forms, the importance of publishing and publications in the process of museum functioning; to scrutinize the general features of this activity: section of publishing, incumbencies, stages of publishing projects realization, sponsorship, companions, characteristics of publications. In the process of writing, special literature, different articles of Lithuanian and foreign researchers and information of the Internet were used. A lot of facts were, given by employees of the museums. The statistics were taken from the section of Information Society Development in the Ministry of Culture, which every year collects this information and publishes it in the portal www.muziejai.lt. The article could be useful not only for academic society, but also for various specialists of culture.